Religious Trauma and Social Identity af Santri: A Qualitative Study In A Pesantren Environment - Zakiyah, Himmatuz (Journal Of Middle East and Islamic Studies, 2026)
This qualitative study examines religious trauma experiences among Santri in a modern Indonesian pesantren, focusing on how teachers weaponize Qur'anic verses and hadiths as tools of symbolic violence. Data were collected through semi structured interviews with five Santri and alumni from Bumi Shalawat Islamic Boarding School, a pseudonym. Findings reveal that selective quotation, decontextualization, and threat based hermeneutics, which I term scriptural violence, are systematically used to enforce conformity, suppress doubt, and induce shame. This scriptural violence operates through three mechanisms. Theological gaslighting denies Santri's interpretive agency. Eschatological blackmail threatens divine punishment. Prophetic proof texting misuses hadiths to legitimize authoritarian pedagogy. Using Bourdieu's concepts of symbolic capital, habitus, doxa, and symbolic violence, the study shows how sacred texts become instruments of terror, producing long term spiritual injury, religious avoidance, and a fractured relationship with God. The study advocates for trauma informed hermeneutics and pedagogical reforms that replace fear based scriptural enforcement with ethical, dialogical religious education. Keywords: Religious trauma, symbolic violence, pesantren.